2010
DOI: 10.3763/ijas.2009.0466
|View full text |Cite
|
Sign up to set email alerts
|

The multifunctional use of urban greenspace

Abstract: This paper draws the attention to the use of urban land use as a promising and new playground for urban green space design, including viable small-scale agricultural activities. First, an overview of urban green space planning is given, followed by a typology of approaches to evaluate urban green space. Next, the specific importance of urban green space for small-scale agriculture and horticulture is highlighted. The paper concludes with an elaboration of the rich multi-tasking performance of urban green space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 5 publications
(9 reference statements)
0
55
0
5
Order By: Relevance
“…In 1996, the United Nations Development Program estimated that 800 million people are engaged in urban and peri-urban agriculture worldwide, a quarter of whom are market producers, employing 150 million people full-time and producing 15 % of the world's food (FAO/WB 2008). Numerous modern cities contain extensive urban agriculture systems, including Shanghai, China, where 60 % of the vegetables and 90 % of the eggs consumed by residents are produced within the city (Bhatt and Farah 2009), and Amsterdam, which contains over 350 hectares of land devoted to urban gardens (van Leeuwen et al 2010). Urban agriculture has been shown repeatedly to contribute to food security through providing nutrient-dense food directly, as well as income from produce sales and employment (e.g., FAO 2008;Dubbeling et al 2009;Zezza and Tasciotti 2010;De Zeeuw et al 2011).…”
Section: Food Securitymentioning
confidence: 99%
“…In 1996, the United Nations Development Program estimated that 800 million people are engaged in urban and peri-urban agriculture worldwide, a quarter of whom are market producers, employing 150 million people full-time and producing 15 % of the world's food (FAO/WB 2008). Numerous modern cities contain extensive urban agriculture systems, including Shanghai, China, where 60 % of the vegetables and 90 % of the eggs consumed by residents are produced within the city (Bhatt and Farah 2009), and Amsterdam, which contains over 350 hectares of land devoted to urban gardens (van Leeuwen et al 2010). Urban agriculture has been shown repeatedly to contribute to food security through providing nutrient-dense food directly, as well as income from produce sales and employment (e.g., FAO 2008;Dubbeling et al 2009;Zezza and Tasciotti 2010;De Zeeuw et al 2011).…”
Section: Food Securitymentioning
confidence: 99%
“…In addition to its environmental side, urban green areas also have economic, aesthetic, social and psychological benefits [2,3]. Thanks to a range of benefits in various forms and a variety of opportunities within cities which they have provided, urban green areas further fulfil a number of functions in an urban context as a comprehensive tool for the long term protection of environmental sustainability through improving the basic conditions of daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Van den Berg et al [11] in a study in the Netherlands, add that access to green space can help residents cope better with stressful life events, especially those related to poverty. With regard to food security, studies have shown that home gardens and community gardens in low income areas are the most economic and readily available sources of nutrition [12][13][14]. Thus, it seems possible that greenery within neighbourhoods is of great importance in the context of urban poverty.…”
Section: Introductionmentioning
confidence: 99%